CREACIÓN DE UN ENTORNO VIRTUAL DE LOS ATRACTIVOS TURÍSTICOS DE LA CIUDAD DE ZARUMA - Romero Jaramillo, Luis Andrés (2021)
The main objective of this research work is to create a virtual environment of the tourist attractions of the city of Zaruma, for which three specific objectives were raised. For the first objective "Identify the potential attractions of Zaruma for the implementation of a virtual environment in the Municipal GAD ITur", the methodology of inventory of attractions was used through inventory cards issued by the Ministry of Tourism (2017), interview with officials del iTur, where it was obtained as a result that the potentially tourist attractions of the city of Zaruma are three: "El Sexmo" Mine, Sanctuary of the Virgen del Carmen, Municipal Museum. For the second objective "Create a more appropriate model to create the virtual environment of the potential attractions of Zaruma for the iTur of the Municipal GAD of Zaruma", the methodology of bibliographic review of studies carried out on Virtual Reality was used, of which it was determined, the Virtual Reality system for total immersion. For the third objective "Determine promotion and dissemination strategies of the virtual environment of the tourist attractions of Zaruma", surveys were applied and four strategies were determined for promotion and dissemination of the virtual environment, a technology and tourism fair to be held in the city of Zaruma , Management of social networks of the Tourist Promotion and Diffusion Unit of the Municipal GAD, placement of billboards in areas of abundant traffic in the country, as well as placement of interactive totems in the land terminals of the cities of Machala, Guayaquil and Quito. Finally, it is concluded that the creation of the virtual environment of the potential tourist attractions of the city of Zaruma is possible, for their respective implementation within the iTur, it can also be established that the city of Zaruma has a high tourist potential that allows it to have a greater tourist flow, achieving a tourist positioning both national and foreign.